2005
DOI: 10.1111/j.1440-1746.2005.03877.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical usefulness of telomerase for the detection of colon cancer in ulcerative colitis patients

Abstract: For the detection of CRC arising in UC, telomerase and hTERT in colonic tissue showed high sensitivity, and telomerase in colonoscopic luminal washings revealed a high specificity. These might be candidate markers in clinical decision making for the diagnosis of CRC from UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
0
12
1
1
Order By: Relevance
“…38,39 In this context, contradictory results have been found in patients with UC. [40][41][42] In our study, the level of hTERT mRNA was significantly increased in CRC samples and in human tumor xenografts but not in the samples of UC patients with and without neoplasia. Thus, our quantitative RT-PCR data, together with previous activity measurements, 40,41 indicate that upregulation of hTERT mRNA does not occur in the early stage of inflammation-dysplasia-carcinoma progression but seems to be associated with the late-stage development of CRC, as suggested by Kanamaru et al 39 Similarly, we can assume that prominent upregulation of the ILK expression occurs during the later stages of colon cancer progression, especially in malignant cell compartments endowed with high invasivity and metastatic potential.…”
Section: Discussioncontrasting
confidence: 51%
“…38,39 In this context, contradictory results have been found in patients with UC. [40][41][42] In our study, the level of hTERT mRNA was significantly increased in CRC samples and in human tumor xenografts but not in the samples of UC patients with and without neoplasia. Thus, our quantitative RT-PCR data, together with previous activity measurements, 40,41 indicate that upregulation of hTERT mRNA does not occur in the early stage of inflammation-dysplasia-carcinoma progression but seems to be associated with the late-stage development of CRC, as suggested by Kanamaru et al 39 Similarly, we can assume that prominent upregulation of the ILK expression occurs during the later stages of colon cancer progression, especially in malignant cell compartments endowed with high invasivity and metastatic potential.…”
Section: Discussioncontrasting
confidence: 51%
“…Whilst telomerase has previously been investigated as a biomarker for colon cancer in resected specimens [15,74], biopsy specimens and luminal washings [27,75] it has not, to our knowledge, been used previously to detect exfoliated colonocytes in faecal samples.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the activity was significantly lower in these cells (30). Also, when telomerase activity was determined in luminal washes, 62% colorectal cancer patients were telomerase-positive, whereas none of normal or ulcerative colitis patients expressed it (23). Similarly, in pancreatic cancer patients, TA in the pancreatic juice was detected in 80% cases and none with chronic pancreatitis (31).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, TA was detected in all esophageal cancers and up to 87% of the noncancerous tissues (25)(26). A recent study has shown that 97% of biopsy specimens from colorectal carcinoma, 67% of ulcerative colitis, and 27% of normal controls expressed telomerase activity (23). The second argument is that determination of the activity of the telomerase enzyme is prior to the determination of the expression of its different components, because even the expression of the rate-limiting hTERT subunit is necessary, but not sufficient for correct assembly of the functional telomerase ribonucleoprotein complex, which is regulated at multiple levels (19,27).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation